2023
DOI: 10.1111/apm.13314
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll‐like receptor 2 rs111200466 polymorphism with low serum levels of IL‐33 in early childhood

Abstract: TLR2 is one of 10 human TLRs, which plays an important role in the recognition of pathogens and activation of the innate immunity via NF‐κB pathway. NF‐κB activation induces the expression of various pro‐inflammatory genes. This study examines the effect of TLR2 polymorphisms on the production of blood pro‐inflammatory cytokines in healthy Finnish children. One hundred forty‐six children who participated in a prospective observational birth cohort study in Turku, Finland, were included. DNA samples were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This finding suggests that children with the polymorphism of TLR2 may have impaired production of IL‐33, which could contribute to the protection against asthma development. However, we did not find similar correlation between TLR2 rs111200466 polymorphism and serum sST2 levels [17]. Here we wanted further to study the effects of these SNPs of ST2 and IL‐33 on serum sST2 and IL‐33 levels and in addition, to investigate whether these polymorphisms are associated with the susceptibility to recurrent wheezing or asthma.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests that children with the polymorphism of TLR2 may have impaired production of IL‐33, which could contribute to the protection against asthma development. However, we did not find similar correlation between TLR2 rs111200466 polymorphism and serum sST2 levels [17]. Here we wanted further to study the effects of these SNPs of ST2 and IL‐33 on serum sST2 and IL‐33 levels and in addition, to investigate whether these polymorphisms are associated with the susceptibility to recurrent wheezing or asthma.…”
mentioning
confidence: 97%
“…We have previously shown with the same cohort that low concentration of serum sST2, but not IL‐33, at early age (13 months) is associated with a higher risk for development of asthma at 7 years of age in Finnish children [16]. In addition, we found that subjects who carry a 23 bp deletion in the promoter of TLR2 (rs111200466) produced lower level of serum IL‐33 compared to those who carry the insertion [17]. This finding suggests that children with the polymorphism of TLR2 may have impaired production of IL‐33, which could contribute to the protection against asthma development.…”
mentioning
confidence: 99%
“…Indeed, TLR2 rs3804100, rs1898830 and rs5743708 single nucleotide polymorphisms, which lead to variations in the amino acid sequence of TLR2, have been related to periodontal tissue destruction (Shan et al, 2020;Takahashi et al, 2011). Recently, TLR2 rs111200466 deletion was revealed to be associated with altered serum IL-33 levels in children (Teräsjärvi et al, 2023). Based on this background information, we hypothesised that there is an association between periodontitis and elevated salivary IL-33 and sST2 levels, and this could be related to the presence of TLR2 rs111200466 polymorphism.…”
mentioning
confidence: 99%